The Falls In Care Home study: a feasibility randomized controlled trial of the use of a risk assessment and decision support tool to prevent falls in care homes. (October 2016) - Walker, Gemma M; Armstrong, Sarah; Gordon, Adam L; Gladman, John; Robertson, Kate; Ward, Marie; Conroy, Simon; Arnold, Gail; Darby, Janet; Frowd, Nadia; Williams, Wynne; Knowles, Sue; et al.
Objective: To explore the feasibility of implementing and evaluating the Guide to Action Care Home fall prevention intervention. Design: Two-centre, cluster feasibility randomized controlled trial and process evaluation. Setting: Purposive sample of six diverse old age/learning disability, long stay care homes in Nottinghamshire, UK. Subjects: Residents aged over 50 years, who had fallen at least once in the past year, not bed-bound, hoist-dependent or terminally ill. Interventions: Intervention homes ( n  = 3) received Guide to Action Care Home fall prevention intervention training and support. Control homes ( n  = 3) received usual care. Outcomes: Recruitment, attrition, baseline and six-month outcome completion, contamination and intervention fidelity, compliance, tolerability, acceptance and impact. Results: A total of 81 of 145 (56%) care homes expressed participatory interest. Six of 22 letter respondent homes (27%) participated. The expected resident recruitment target was achieved by 76% (52/68). Ten (19%) residents did not complete follow-up (seven died, three moved). In intervention homes 36/114 (32%) staff attended training. Two of three (75%) care homes received protocol compliant training. Staff valued the training, but advised greater management involvement to improve intervention implementation. Fall risks were assessed, actioned and recorded in care records. Of 115 recorded falls, 533/570 (93%) of details were complete. Six-month resident fall rates were 1.9 and 4.0 per year for intervention and control homes, respectively. Conclusions: The Guide to Action Care Home is implementable under trial conditions. Recruitment and follow-up rates indicate that a definitive trial can be completed. Falls (primary outcome) can be ascertained reliably from care records.